Summary of grazing research on Kansas conservation reserve program land - Michael R. Langemeier; P.D. Ohlenbusch (Kansas Agricultural Experiment Station Research Reports, 1996)
Animal performance and the net return per acre for four CRP research sites in Kansas in 1994 and 1995 were examined. Both mowing and prescribed burning increased animal performance in 1994. Mowing was economically feasible on one of the four sites. Prescribed burning was economically feasible on three of four sites. Mowing or burning treatments were not repeated in 1995, the second year of the analysis. Second-year animal performance was similar between the untreated plots and those that were mowed or burned in 1994. Net returns per acre for the site that was grazed by cow-calf pairs ranged from -$5.96 to $4.92. For the sites grazed by stockers, net returns per acre varied from -$5.76 to $22.46. The potential seems to be greater for grazing stockers than cow/calf pairs on post-CRP land.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Conservation reserve program; Cow/calf grazing; Stocker grazing